Evaluating the impact of contextual variables on jump shot success in professional basketball: a notational analysis approach - Patterson, J.; Talpey, S. W.; O`Grady, M.; Rayner, R. (International Journal of Performance Analysis in Sport, 2025)
The ability to successfully execute a jump shot is one of the key determinants of success in basketball, and therefore, developing the skill of shooting is a targeted focus for basketball coaches. To optimally design shooting drills, understanding the in-game context in which the skill is executed is required. This study employed a notational analysis of in-game jump shooting performance within Australia`s National Basketball League (NBL) to identify the factors contributing to a successful jump shot. This study analysed the influence of 18 contextual variables, such as shot location, pre-shot movement, use of deception, time of game, and location of defenders, across 877 shot attempts. Findings revealed that time of game, shot clock time, location of shot, and number of passes prior to a shot were key variables that significantly contributed to the outcome of a jump shot. Overall, this notational analysis indicates that a more considered approach can be made regarding shooting drill design and execution. To achieve this, coaches can use the information from this analysis to develop shooting drills that better represent the context in which successful shots are executed during a game.